Hidrossedimentologic study in piquiri river - Queiroz, Manoel Moisés F. de; Angst, Fernando; Gomes, Benedito Martins (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2013)
The objective of this paper was to evaluate the hidrossedimentologic parameters of the Piquiri river and relating them to basin land use systems. They were monitored the parameters of flood and suspension sediment concentrations during the period from August/2007 to April/2008 in Piquiri bridge station, Ubiratã, PR town, BR-369. They determined the rating curve of flood (R2=0,99), rating curve of suspension sediment concentrations (R2=0,95), rating curve of daily total discharge of sediments (R2=0,98) and rating curve of turbidity in function of suspension sediments (R2=0,94), being that all presented good settlements. The results indicated that can be classified in a very decrease it moderated the output of sediments of the basin